How do patients determine when their inhaler is empty? Insights from an analysis of returned inhalers and a patient survey - Jennifer K Quint; Will Carroll; Rachel Malone; Anna C Murphy; Marissa Gotsell; Charles Potter (BMJ Open Respiratory Research)
Background Inhalers are widely used for the management of asthma and chronic obstructive pulmonary disease. However, there is little knowledge about the extent to which an inhaler is used and when it is disposed of, despite the implications for an individual’s health (when used beyond the recommended number of doses (overused)), and medicine wastage, healthcare costs and the environment (when discarded with remaining doses (underused)). To explore inhaler use, we assessed the number of doses remaining in pressurised metered-dose inhalers (pMDIs) returned via a Chiesi Inhaler Recycling scheme.Methods pMDIs were dismantled, and components recycled where possible. Each canister was weighed and the mass of the formulation remaining was calculated. pMDIs were categorised based on number of doses remaining (underused, used, empty (indicating correct use) and overused) and by dose counter presence/absence. A separate online survey was used to obtain patient feedback on inhaler use and disposal behaviours.Results Overall, 2614 pMDIs were analysed (55.9% maintenance, 44.1% reliever inhalers); 1015 (38.8%) had an integrated dose counter. The proportion of pMDIs returned empty was greater for inhalers with dose counters than for those without (51.3% vs 25.1%; p<0.0001); the proportion of pMDIs returned underused was lower for inhalers with dose counters than for those without (5.2% vs 33.2%; p<0.0001). The proportion of pMDIs returned overused was substantial and similar for devices with and without dose counters (34.0% vs 23.2%; p>0.01). Most respondents (55.2%) using devices without a dose counter reported that they were not confident in identifying when their inhaler was empty. Furthermore, many respondents (20.6%) who used inhalers with a dose counter reported continued use beyond ‘zero’.Conclusions Our study suggests that many inhalers are returned underused or overused, with inadequate knowledge among patients about the number of therapeutic doses remaining in the device and appropriate inhaler disposal. These have concerning implications for patient health and the environment and highlight a need for high-quality education for patients and healthcare professionals.